(untitled) (CIPEEX, 2024)
GRADING ANSWER SHEETS HAS ALWAYS BEEN A TASK THAT REQUIRES A SIGNIFICANT AMOUNT OF TIME TO COMPLETE. IN THE PAST, IT WAS DONE ENTIRELY MANUALLY, EITHER BY THE TEACHER THEMSELVES OR WITH THE ASSISTANCE OF A HELPER. IT WAS AN EXTREMELY SLOW AND TEDIOUS PROCESS. THEREFORE, WITH THE ADVANCEMENT OF SCIENCE AND INFORMATION TECHNOLOGIES, TOOLS WERE CREATED TO ASSIST EDUCATORS. THE PRIMARY TOOLS CREATED USE OPTICAL AND ELECTRONIC TECHNIQUES FOR GRADING ANSWER SHEETS. THERE ARE VARIOUS TYPES OF GRADING TOOLS AVAILABLE IN THE MARKET. SOME ARE DESIGNED SOLELY FOR GRADING ANSWER SHEETS, WHILE OTHERS ARE COMPREHENSIVE PLATFORMS THAT ENCOMPASS ALL THE NECESSARY FUNCTIONALITIES FOR GRADING EXAMS, RECORDING GRADES, AND GENERATING COMPLEX REPORTS.